Um “lugar para ser”: reconstruções identitárias de pessoas LGBTQIA+ cristãs nas Igrejas da Comunidade Metropolitana - Dias, Tainah Biela (2022)
The thesis proposed to investigate the socio-religious experiences of LGBTQIA+ Christian people who, at a certain point in their trajectories, adhere to the theological-pastoral proposal of the Metropolitan Community Churches in Brazil. More specifically, we focus on the local communities of São Paulo and Teresina in order to understand how these religious communities help in the processes of reconciliation between sexual and/or gender identity and Christian religiosity. Thus, we start from a conceptualization of religious modernity to analyze the processes that allow the relative autonomy of religious people in search of faith alternatives that contemplate their own experiences. We could see how the processes of identity reconstruction and reconciliation of Christian faith and LGTBQIA+ identity occur, albeit in an incipient way, even before finding the local communities of the MCCs. However, the possibility of affirming oneself as an LGBTQIA+ and Christian person will only be possible due to the encounter with a religious community that legitimizes new possibilities in the field of identity categories. Through interviews with members and religious leaders from the local communities of São Paulo and Teresina, we were able to understand the ways in which the MCCs are able to promote important resignifications that reverberate in the reconstruction of the subjectivities of our research interlocutors. Furthermore, we consider the political-religious impacts of a faith community that claims for itself an identity that is historically denied to LGBTQIA+ people, thus producing effects that go beyond the walls of local congregations and insert new debates and tensions in the Brazilian wider religious landscape.(AU)